A review on biomolecular immobilization of polymeric textile biocomposites, bionanocomposites, and nano-biocomposites. Issue 9 (2nd September 2022) - Idumah, Christopher Igwe; Ezika, Anthony Chidi; Enwerem, Uzoma Ebenezer
Abstract: Recently, comingling of natural fibers (NFs) derived from renewable resources, and nanoparticles with synthetic and biopolymeric matrices has resulted in fabrication of NF biocomposites, nanobiocomposites, and bionanocomposites (NFB). The quests to inculcate biomedical behavior to these materials have resulted in immobilization of biomolecules such as bioactive peptides, plant extracts/essential oils, ligands, enzymes, and so on, via varying techniques, within these materials, to attain antibacterial, anticancerous, antispasmotic, antidiabetic, anticough, antiviral, anti-inflammatory, antioxidant, antiarthritic, analgesic, antibiotic, antiatherogenic, antiulcer, antipyretic, immunomodulatory, as well as, chemo-preventive behaviors suitable for drug delivery and biomedicals. Therefore, this article presents a general overview of novel trends in fabricating NFB for biomedical applications with emphasis on varying approaches of immobilizing bioactive molecules, as well as chemically and physically affiliated modification techniques enhancing the fabrication of polymeric textiles biocomposites, nanobiocomposites, and bionanocomposites.